If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -7 = 54t Reorder the terms: -7 + 5t = 54t Solving -7 + 5t = 54t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-54t' to each side of the equation. -7 + 5t + -54t = 54t + -54t Combine like terms: 5t + -54t = -49t -7 + -49t = 54t + -54t Combine like terms: 54t + -54t = 0 -7 + -49t = 0 Add '7' to each side of the equation. -7 + 7 + -49t = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -49t = 0 + 7 -49t = 0 + 7 Combine like terms: 0 + 7 = 7 -49t = 7 Divide each side by '-49'. t = -0.1428571429 Simplifying t = -0.1428571429
| 3(80-8x)=x-96 | | 2/3+5/15 | | 0=-5/4(y-6/5) | | 16/24=x/12 | | 3x-7/6=4x-7/6 | | -9(x+p)=x | | -13=17+x | | 3x-4=5(x+2) | | 4/5=n/20 | | (x+1)(x+3)=2(x+3) | | 2x+2/x-5=6 | | 5+(x-2/3)=(x+3/8) | | x2+2/x-5 | | 4x+9x=-39 | | b=7/4(j-49) | | 4x+2/2=17 | | 6x-2/5=8 | | 392+2x^2=1168 | | 3d=4(x-2) | | 18y+55x=2791 | | 1/55x+1/66x=1 | | -16-(-21)=x/6 | | 8x+20=3x+100 | | 1/2(4x+6)=1/3(9x-24) | | (5-y)-(6-y)=0 | | 9x-9/3=21 | | y=0.3x^2-4x+0.5 | | -5-2=13 | | 20x-10=14x+12 | | 4y+17=5x-4 | | -5x-2=1 | | 2x+42+1x-24=180 |